Prevalence of hypertension among school children in Kashmir, India - Bhat, Rais A.; Wani, Wasim A.; Dar, Sheeraz A.; Wani, Khurshid A. (International Journal of Research in Medical Sciences, 2019)
Background: Over the last two decades, there has been increased awareness that hypertension in children may be a part of the spectrum of essential hypertension mainly linked to obesity epidemic. An increasing number of children and adolescents are being diagnosed with hypertension. Objectives of this study was to determine the prevalence of hypertension among apparently healthy school children residing in the valley of Kashmir. Methods: It was a community based cross sectional study was done over a period of one year in School going children aged 11 to 16 years from both urban and rural areas of Kashmir valley. Results: Thus, prevalence of hypertension was 5.1% and prevalence of prehypertension was 9.3%. Out of total 1600 children 1464 (91.5%) had a normal BMI, 72 (4.5%) were overweight and 64 (4%) were obese. In the prehypertensive group 114 (77%) had normal BMI, 18 (12.16%) were overweight and 16 (10.8%) were obese. In the hypertensive group 30 (36.6%) had normal BMI, 26 (31.7%) were overweight and 26 (31.7%) were obese. Conclusions: Our study reveals that hypertension is not uncommon in Kashmiri children. With globalization bringing more lifestyle modifications, children are exposed to multiple risk factors including obesity and family history of hypertension. We need to make people aware of these facts so that blood pressure measurement could be a part of routine health care check-up in children to detect it early and do necessary interventions.